Preparation method and application of green and environment-friendly hard carbon material
By replacing traditional strong acid or strong alkali treatment methods with metal salt solutions, green and environmentally friendly hard carbon materials are prepared, which solves the problems of environmental pollution and high production costs in the existing processes, and achieves the preparation of high-performance and environmentally friendly hard carbon materials.
Patent Information
- Application Number
- CN202411940659.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
The use of strong acid or strong alkali treatment methods in the existing hard carbon material preparation process leads to high environmental pollution and production costs, and it is difficult to effectively solve the problems of structural regulation, performance optimization and stability improvement.
Metal salt solution is used to replace traditional strong acid or strong alkali treatment methods, and green and environmentally friendly hard carbon materials are prepared through steps such as crushing, soaking, rinsing, drying and carbonization.
It significantly improves the environmental protection of the preparation process, simplifies the process flow, reduces production costs, and the resulting hard carbon material has high energy density, long cycle life and good electrochemical properties.
Smart Images

Figure CN119706802A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of hard carbon materials, and in particular to a preparation method and application of a green and environment-friendly hard carbon material. Background Art
[0002] With the surge in global energy demand and the increasing attention to environmental protection, the development of sustainable and environmentally friendly energy storage technologies is particularly urgent. In this context, sodium-ion batteries, as a low-cost, resource-rich and environmentally friendly energy storage technology, have gradually become the focus of the research community. Among them, hard carbon materials have become a research hotspot for negative electrode materials of sodium-ion batteries due to their unique structure and properties. Hard carbon materials, a type of graphene sheet structure with short-range ordered arrangement, have a unique microstructure that provides a large amount of embedding space and fast diffusion channels for sodium ions, enabling them to exhibit extremely high energy density and excellent cycle performance in sodium-ion batteries.
[0003] Hard carbon materials have various preparation methods, a wide range of raw material sources, and a large modification and regulation space, which provides the possibility for the commercial application of high-performance sodium-ion batteries. However, the application of hard carbon materials in sodium-ion batteries still faces many challenges, such as structural regulation, performance optimization, and stability improvement. Therefore, in-depth research on the structure and sodium storage mechanism of hard carbon materials, and exploration of their preparation process and modification methods are of great significance for promoting the widespread application of sodium-ion batteries in the field of energy storage.
[0004] The Chinese patent document with the authorization announcement number CN116621157B discloses a preparation method, hard carbon material and application of a hard carbon material. The specific preparation method includes: S1, crushing the wood part of the wood to obtain a wood block; S2, placing the obtained wood block in an alkaline solution with a mass fraction of 3%-6%, and performing a hydrothermal reaction at 90-00℃, taking out the wood block, and washing the wood block with water until the pH of the washing liquid is 6.8-7.2; S3, soaking the washed wood block in methanol and / or ethanol for 3-5h, taking out the wood block, and air-drying until no liquid drips; S4, heating the obtained air-dried wood block to 1000-1200℃ in an inert atmosphere at a heating rate of 2-4℃ / min for carbonization for 3-6h, and cooling to obtain a hard carbon material.
[0005] Biomass materials (such as plant residues, agricultural waste, etc.) have the advantages of wide sources and low costs, and are usually used to prepare hard carbon that can be used as negative electrode materials for secondary energy storage batteries. The existing preparation process of biomass hard carbon usually involves converting biomass into carbon materials through pyrolysis or other chemical processes. In this process, the use of acid or alkali to treat the raw materials is often used to improve the structure and properties of the material. However, in large-scale applications, this treatment method makes the equipment of the treatment process more complicated and increases the corresponding production cost. It also produces harmful by-products that cause environmental pollution, which increases the production cost of the material and faces corresponding environmental problems. Summary of the invention
[0006] In view of the problems existing in the background technology, a preparation method and application of green and environmentally friendly hard carbon materials are proposed. Metal salt solution is used instead of traditional strong acid and strong alkali treatment methods, which fundamentally avoids the use of harmful chemicals and the production of toxic by-products, and greatly improves the environmental friendliness of the preparation process.
[0007] The present invention provides a method for preparing a green and environmentally friendly hard carbon material, the steps comprising:
[0008] S1. Crushing biomass agricultural waste;
[0009] S2, soaking the crushed debris in a salt solution;
[0010] S3, rinsing the soaked debris and drying it;
[0011] S4. The dried debris is carbonized in a specific atmosphere to obtain a hard carbon material.
[0012] Preferably, the biomass agricultural waste in S1 is selected from one or more of crops, straw, fruit shells, fruit residues, forestry waste and other agricultural waste.
[0013] Preferably, the biomass agricultural waste in S1 is processed and the obtained material has a particle size D50 < 50 μm.
[0014] Preferably, the salt used in S2 is a common metal inorganic salt; the mass ratio of biomass debris to metal salt is (100-5):1; the mass fraction of the salt solution is 3%-20%; and the treatment is carried out at room temperature for 0.5-15 days.
[0015] Preferably, during the cleaning in S3, the treated debris needs to be dispersed and centrifuged in deionized water for multiple times.
[0016] Preferably, the temperature control range of the material drying process in S3 is 40-150°C.
[0017] Preferably, the carbonization temperature in S4 includes several stages including 200-400°C, 400-600°C, and 1000-1500°C, and the total carbonization reaction time is 4-24h.
[0018] Preferably, the special gas atmosphere in S4 is selected from argon or nitrogen.
[0019] The present invention further proposes a green and environmentally friendly hard carbon material, which is prepared by the above-mentioned green and environmentally friendly hard carbon material preparation method; the particle size of the obtained hard carbon material is ≤20μm, the pore size of the sodium storage active pores in the hard carbon material is 0.1-25nm, and the specific surface area of the hard carbon material is ≤30m 2 / g.
[0020] The present invention further proposes an application of a green and environmentally friendly hard carbon material, and applies the green and environmentally friendly hard carbon material to negative electrode materials for secondary batteries.
[0021] Compared with the prior art, the present invention has the following beneficial technical effects: First, the present invention adopts metal salt solution to replace the traditional strong acid and strong alkali treatment methods, which fundamentally avoids the use of harmful chemicals and the production of toxic by-products, and greatly improves the environmental friendliness of the preparation process. The entire process is simple and efficient, without environmental pollution, and meets the requirements of green and sustainable development. Secondly, the present invention utilizes biomass waste such as crop waste, fruit shells, bamboo, etc. as raw materials to realize waste resource utilization, which not only reduces the cost of raw materials, but also reduces dependence on natural resources, and provides the possibility for large-scale industrial applications. The preparation process only involves the steps of crushing, soaking, rinsing, drying and carbonization, avoiding the need for complex chemical modification or special equipment. The process flow is simple and efficient, which is conducive to industrial production and further reduces production costs. Finally, the particle size of the hard carbon material obtained is ≤20μm, the pore size of the sodium storage active pores in the hard carbon material is 0.1-25nm, and the specific surface area of the hard carbon material is ≤30m 2 / g, the material has an ideal reversible specific capacity (>310mAh g -1 ), high ICE (>85%), and long cycle life (>1000 cycles), showing significant advantages in electrochemical performance. These performance improvements make sodium ion embedding and diffusion more efficient, thereby meeting the actual needs of high-performance sodium ion batteries. Therefore, the present invention combines the recycling of biomass waste with the preparation process of green materials, providing a sustainable development solution for the large-scale production of hard carbon materials and the development of new energy fields, which has important industrial application value and social significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of a hard carbon material prepared by the method for preparing a green and environmentally friendly hard carbon material in Example 1. DETAILED DESCRIPTION
[0023] Example 1
[0024] This embodiment provides a method for preparing a green and environmentally friendly hard carbon material, and the steps are as follows:
[0025] 1) uniformly crushing the dried hazelnut shell waste;
[0026] 2) The crushed debris was passed through a 200-mesh sieve and then immersed in a 3% by mass NaHCO3 solution for 0.5 days;
[0027] 3) The treated powder is rinsed with deionized water and ethanol respectively, and then placed in a forced air drying oven for air drying;
[0028] 4) The dried sample was gradually heated to 300°C and 1200°C at a heating rate of 2°C / min in an inert gas Ar atmosphere for step carbonization. The carbonization was performed at each temperature for 3 hours, and then naturally cooled to room temperature to obtain a hard carbon material.
[0029] Example 2
[0030] This embodiment provides a method for preparing a green and environmentally friendly hard carbon material, comprising the steps of:
[0031] 1) uniformly crushing the dried wheat husk;
[0032] 2) The crushed debris was passed through a 200-mesh sieve and then immersed in a 5% by mass NaHCO3 solution for 3 days;
[0033] 3) The treated powder is rinsed with deionized water and ethanol respectively, and then placed in a forced air drying oven for air drying;
[0034] 4) The dried sample was gradually heated to 400°C and 1300°C at a heating rate of 3°C / min in an inert gas Ar atmosphere for step carbonization. The carbonization was performed at each temperature for 3 hours, and then naturally cooled to room temperature to obtain a hard carbon material.
[0035] Example 2
[0036] This embodiment provides a method for preparing a green and environmentally friendly hard carbon material, comprising the steps of:
[0037] 1) uniformly crushing the dried peanut shells;
[0038] 2) The crushed debris was passed through a 200-mesh sieve and then immersed in a 7% by mass ZnCl2 solution for 7 days;
[0039] 3) The treated powder is rinsed with deionized water and ethanol respectively, and then placed in a forced air drying oven for air drying;
[0040] 4) The dried sample was gradually heated to 400°C, 600°C, and 1300°C at a heating rate of 2°C / min in an inert gas Ar atmosphere for step carbonization. The sample was carbonized at each temperature for 2 hours and then naturally cooled to room temperature to obtain a hard carbon material.
[0041] Example 4
[0042] This embodiment provides a method for preparing a green and environmentally friendly hard carbon material, comprising the steps of:
[0043] 1) uniformly crushing the dried melon seed shells;
[0044] 2) The crushed debris was passed through a 200-mesh sieve and then immersed in a 10% by mass ZnCl2 solution for 10 days;
[0045] 3) The treated powder is rinsed with deionized water and ethanol respectively, and then placed in a forced air drying oven for air drying;
[0046] 4) The dried sample was gradually heated to 400°C, 600°C, and 1300°C at a heating rate of 5°C / min in an inert gas Ar atmosphere for step carbonization. The sample was carbonized at each temperature for two hours and then naturally cooled to room temperature to obtain a hard carbon material.
[0047] Example 5
[0048] This embodiment provides a method for preparing a green and environmentally friendly hard carbon material, comprising the steps of:
[0049] 1) uniformly crushing the dried hazelnut shells;
[0050] 2) The crushed debris was passed through a 200-mesh sieve and then immersed in a 15% by mass CuSO4 solution for 10 days;
[0051] 3) The treated powder is rinsed with deionized water and ethanol respectively, and then placed in a forced air drying oven for air drying;
[0052] 4) The dried sample was gradually heated to 400°C at a heating rate of 2°C / min in an inert gas Ar atmosphere and carbonized for two hours. Thereafter, the temperature was increased to 1300°C at a heating rate of 5°C / min and carbonized for three hours. The sample was then naturally cooled to room temperature to obtain a hard carbon material.
[0053] Example 6
[0054] This embodiment provides a method for preparing a green and environmentally friendly hard carbon material, comprising the steps of:
[0055] 1) uniformly crushing the dried almond shell waste;
[0056] 2) The crushed debris was passed through a 200-mesh sieve and then immersed in a 20% by mass CuSO4 solution for 15 days;
[0057] 3) The treated powder is rinsed with deionized water and ethanol respectively, and then placed in a forced air drying oven for air drying;
[0058] 4) The dried sample was gradually heated to 400°C at a heating rate of 4°C / min in an inert gas Ar atmosphere and carbonized for 1 hour. Thereafter, the sample was heated to 1400°C at a heating rate of 5°C / min and carbonized for 4 hours. After the carbonization, the sample was naturally cooled to room temperature to obtain a hard carbon material.
[0059] Comparative Example 1
[0060] This comparative example provides a method for preparing a green and environmentally friendly hard carbon material. The preparation method is similar to the steps in Example 1, except that steps 2 and 3 in Example 1 are not performed, and specifically includes:
[0061] 1) The dried hazelnut shell waste is uniformly crushed, then sieved with 200 mesh and dried;
[0062] 2) The dried sample was gradually heated to 300°C and 1200°C at a heating rate of 2°C / min in an inert gas Ar atmosphere for step carbonization. The carbonization was performed at each temperature for 3 hours, and then naturally cooled to room temperature to obtain a hard carbon material.
[0063] Comparative Example 2
[0064] This comparative example provides a method for preparing a green and environmentally friendly hard carbon material. The preparation method is similar to the steps in Example 1, with the only difference being that in step 4 in Example 1, the temperature is gradually increased to 1200°C at a heating rate of 2°C / min and maintained at a constant temperature for 6 hours to implement one-step carbonization, and then naturally cooled to room temperature to obtain a hard carbon material.
[0065] Comparative Example 3
[0066] This comparative example provides a method for preparing a green and environmentally friendly hard carbon material. The preparation method is similar to the steps in Example 3, except that steps 2 and 3 in Example 3 are not performed, and the carbonization process of step 4 is modified, specifically comprising:
[0067] 1) uniformly crushing the dried peanut shells, then sieving through 200 mesh and drying;
[0068] 2) The dried sample was gradually heated to 1300°C at a heating rate of 5°C / min in an inert gas Ar atmosphere for step carbonization for 6 hours, and then naturally cooled to room temperature to obtain a hard carbon material.
[0069] Comparative Example 4
[0070] This comparative example provides a method for preparing a green and environmentally friendly hard carbon material. The preparation method is similar to the steps in Example 4, except that steps 2 and 3 in Example 4 are not performed, and specifically includes:
[0071] 1) uniformly crushing the dried melon seed shells, then sieving them through 200 meshes and drying them;
[0072] 2) The dried sample was gradually heated to 400°C, 600°C, and 1300°C at a heating rate of 5°C / min in an inert gas Ar atmosphere for step carbonization. The sample was carbonized at each temperature for two hours and then naturally cooled to room temperature to obtain a hard carbon material.
[0073] Comparative Example 5
[0074] This comparative example provides a method for preparing a green and environmentally friendly hard carbon material. The preparation method is similar to the steps in Example 5, except that the treatment time and concentration of step 2 in Example 5 are adjusted, specifically comprising:
[0075] 1) uniformly crushing the dried hazelnut shells;
[0076] 2) The crushed debris was passed through a 200-mesh sieve and then immersed in a 5% CuSO4 solution at a temperature of 50°C for 5 days;
[0077] 3) The treated powder is rinsed with deionized water and ethanol respectively, and then placed in a forced air drying oven for air drying;
[0078] 4) The dried sample was gradually heated to 400°C at a heating rate of 2°C / min in an inert gas Ar atmosphere and carbonized for two hours. Thereafter, the temperature was increased to 1300°C at 5°C / min and carbonized for three hours. The sample was then naturally cooled to room temperature to obtain a hard carbon material.
[0079] Comparative Example 6
[0080] This comparative example provides a method for preparing a green and environmentally friendly hard carbon material. The preparation method is similar to the steps in Example 6, except that the treatment time and concentration of step 2 in Example 6 and the carbonization process of step 4 are adjusted, as follows:
[0081] 1) uniformly crushing the dried almond shell waste;
[0082] 2) The crushed debris was passed through a 200-mesh sieve and then immersed in a 10% CuSO4 solution at a temperature of 10°C for 10 days;
[0083] 3) The treated powder is rinsed with deionized water and ethanol respectively, and then placed in a forced air drying oven for air drying;
[0084] 4) The dried sample was gradually heated to 1400°C at a heating rate of 2°C / min in an inert gas Ar atmosphere and carbonized for 4 hours. After the carbonization, the sample was naturally cooled to room temperature to obtain a hard carbon material.
[0085] Next, the present invention conducts relevant performance tests on the green and environmentally friendly hard carbon material prepared by the method in the above embodiment, and the test contents include SEM test, physical and chemical performance test, and button battery test.
[0086] (1) SEM test: The principle of SEM test is to use a finely focused electron beam to scan the sample surface. The electrons interact with the sample to stimulate various physical information (such as secondary electrons, backscattered electrons, X-rays, etc.). This information is collected, amplified, and then imaged to obtain an observation of the sample surface morphology. The steps of SEM test usually include sample preparation, sample processing, machine operation, and image acquisition.
[0087] The present invention uses the method in Example 1 to prepare the hard carbon material for SEM testing. The test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the hard carbon material has a uniform size distribution, a smooth surface, and a small amount of adsorbed fine powder. The particle size of the hard carbon material is between 5-20 μm.
[0088] (2) Physical and chemical performance testing: Physical and chemical performance testing is a series of test methods to evaluate the physical and chemical properties of materials or products. These tests help to understand the basic properties of materials or products, and then provide a scientific basis for their application in specific fields.
[0089] The present invention refers to the method in the national standard GB / T 43114-2023 "Hard Carbon" to test the specific surface area of the hard carbon material obtained in the embodiment and the comparative example, and tests the diffusion coefficient of the material by GITT and the particle size La by XRD. The test results are shown in Table 1.
[0090] (3) Button battery testing: Button battery testing is an important step in ensuring the quality, safety and performance of button batteries. The testing methods for button batteries usually include laboratory testing and practical application testing. Laboratory testing mainly uses professional testing equipment and instruments to accurately measure and analyze the various performance indicators of button batteries. Practical application testing is to observe and evaluate the performance of button batteries in actual use environments. Button battery testing needs to follow certain standards to ensure the accuracy and comparability of test results. These standards are usually formulated by industry associations, government agencies or professional organizations, and cover various performance indicators and testing methods of button batteries. Common button battery testing standards include QB / T1759-1993 "Button Battery Assembly Line", HDB / QB030-2008 "LR44 Alkaline Zinc-Manganese Button Battery Processing Trade Unit Consumption Standard", QB / T 3747-1999 "Alkaline Manganese Button Battery", etc.
[0091] The present invention uses the hard carbon materials obtained in Examples 1-6 and Comparative Examples 1-6 as negative electrode materials for sodium ion batteries, and assembles them into button batteries. The specific preparation method of the negative electrode material is: a negative electrode sheet is prepared according to a mass ratio of hard carbon material: binder CMC: conductive agent Super P of 8:1:1; a sodium sheet is used as a counter electrode; NaPF6 (solvent is diethylene glycol dimethyl ether, concentration is 1 mol / L) is used as the electrolyte; and the diaphragm is a glass fiber diaphragm. The button battery is assembled in an argon-filled glove box. The electrochemical performance is carried out on a Xinwei CT-4008Tn battery tester, with a charge and discharge voltage range of 0.01V to 2.5V and a charge and discharge rate of 60mAg -1 , tested the first cycle discharge capacity, first charge and discharge efficiency, and charging DCR (50% SOC, 60mA g -1 )、Capacity retention rate (300mA g -1 ,1000 weeks), the test results are shown in Table 1.
[0092] Table 1 Physical and chemical properties of hard carbon materials
[0093]
[0094]
[0095] As shown in Table 1, by analyzing the specific surface area, diffusion coefficient and particle size La data of the hard carbon material, it is concluded that the performance of the hard carbon material in Examples 1-6 is better than that of the hard carbon material in Comparative Examples 1-6. By analyzing the first cycle discharge capacity, first charge and discharge efficiency and charging DCR data, it is concluded that the button cell in Examples 1-6 is better than that of the button cell in Comparative Examples 1-6.
[0096] The preparation method of the green and environmentally friendly hard carbon material provided by the present invention firstly grinds the biomass agricultural product waste crops, fruit shells, bamboo, etc. into debris by means of a pulverizer or ball mill, and then places the debris in a certain metal salt solution for pretreatment, so that the cellulose, hemicellulose and lignin contained in the biomass material debris are decomposed, and the organic long-chain macromolecules are degraded into small molecules, and some impurities are removed to optimize the original structure. Then, a uniform pore structure is formed through a subsequent heat treatment process to produce a suitable short-range graphite domain structure. Finally, a relatively ideal charge specific capacity (>320mAh g -1 ), higher initial charge and discharge efficiency (>85%), and more than 89% capacity retention after 1000 cycles. Therefore, compared with the traditional hard carbon material preparation method, the hard carbon material prepared by the present invention shows significant advantages in electrochemical performance. These performance improvements come from the optimized microstructure design, which makes the sodium ion embedding and diffusion more efficient, thus meeting the actual needs of high-performance sodium ion batteries.
[0097] In addition, compared with traditional strong acid and strong alkali treatment processes, the present invention significantly reduces the demand for corrosion-resistant equipment, simplifies equipment design, and reduces energy consumption and wastewater treatment costs. Through efficient green processes, the present invention not only achieves environmentally friendly hard carbon material production, but also significantly improves economic benefits. Finally, the present invention fully combines the recycling of biomass waste with green preparation technology, providing a sustainable development solution for the large-scale production of hard carbon materials and the development of new energy fields, which has important industrial application value and social significance.
[0098] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited thereto, and various changes can be made within the knowledge scope of technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing a green and environmentally friendly hard carbon material, characterized in that the steps include: S1. Crushing biomass agricultural waste; S2, soaking the crushed debris in a salt solution; S3, rinsing the soaked debris and drying it; S4. The dried debris is carbonized in a specific atmosphere to obtain a hard carbon material.
2. The method for preparing a green and environmentally friendly hard carbon material according to claim 1, characterized in that: The biomass agricultural waste in S1 is selected from one or more of crops, straw, fruit shells, fruit residues, forestry waste and other agricultural waste.
3. The method for preparing a green and environmentally friendly hard carbon material according to claim 1, characterized in that: In S1, biomass agricultural waste is processed and the obtained material particle size D50 is less than 50 μm.
4. The method for preparing a green and environmentally friendly hard carbon material according to claim 1, characterized in that: The salt used in S2 is a common metal inorganic salt; the mass ratio of biomass debris to metal salt is (100-5):1; the mass fraction of the salt solution is 3%-20%; and the treatment is carried out at room temperature for 0.5-15 days.
5. The method for preparing a green and environmentally friendly hard carbon material according to claim 1, characterized in that: During the cleaning in S3, the processed debris needs to be dispersed and centrifuged in deionized water for multiple times.
6. The method for preparing a green and environmentally friendly hard carbon material according to claim 1, characterized in that: The temperature control range of the material drying process in S3 is 40-150℃.
7. The method for preparing a green and environmentally friendly hard carbon material according to claim 1, characterized in that: The carbonization temperature in S4 includes several stages including 200-400°C, 400-600°C, and 1000-1500°C, and the total carbonization reaction time is 4-24h.
8. The method for preparing a green and environmentally friendly hard carbon material according to claim 1, characterized in that: The special gas atmosphere in S4 is selected from argon or nitrogen.
9. A green and environmentally friendly hard carbon material, characterized in that: The hard carbon material is prepared by the preparation method of the green and environmentally friendly hard carbon material according to any one of claims 1 to 8; the particle size of the hard carbon material is ≤20 μm, the pore size of the sodium storage active pores in the hard carbon material is 0.1-25 nm, and the specific surface area of the hard carbon material is ≤30 m 2 / g.
10. An application of a green and environmentally friendly hard carbon material, characterized in that: The green and environmentally friendly hard carbon material according to claim 9 is applied to negative electrode materials for secondary batteries.
Citation Information
Patent Citations
A method for preparing hard carbon materials, hard carbon materials and their applications
CN116621157B